Application of endurance time method to seismic fragility evaluation of highway bridges considering scour effect. Issue 136 (September 2020) - He, Haifeng; Wei, Kai; Zhang, Jiarui; Qin, Shunquan
Abstract: Earthquake and flood scour are two main causes of failures to highway bridges. This study developed an alternative fragility analysis framework of bridges based on endurance time method (ETM). A two-span reinforced concrete highway bridge supported by three types of substructures, e.g. shaft foundation, two-column bent foundation and pile group foundation, was taken as the example bridge. The developed framework was used to obtain the fragility curves of the example bridges. The influences of scour depth, substructure design, ground motion direction and scour countermeasure on the seismic fragility of bridges were investigated. The developed seismic fragility analysis framework based on endurance time method yields accurate and efficient calculation compared with IDA method. Scour reduces the bearing capacity of the foundation and affects the seismic fragility of bridges. However, the effect of scour on the seismic fragility varies with the bridge substructure design, the ground motion direction and the application of the scour countermeasure. Highlights: Seismic fragility analysis framework based on endurance time method is developed and validated for bridge. Seismic fragility of the example bridge supported by different substructures are analyzed. The effect of scour on the seismic fragility for different damage states are investigated. The influence of substructure design, ground motion direction and scour countermeasures are discussed.